A neural mechanism for affective well-being: subgenual cingulate cortex mediates real-life effects of nonexercise activity on energy - Reichert, Markus; Braun, Urs; Gan, Gabriela; Reinhard, Iris; Giurgiu, Marco; Ma, Ren; Zang, Zhenxiang; Hennig, Oliver; Koch, Elena; Wieland, Lena; Schweiger, Janina; Inta, Dragos; et al. (Science advances, 2020)
Physical activity substantially improves well-being and mental health, but the underlying brain processes remain unclear. Most research concerns exercise, although the majority of everyday human behaviors, such as walking or stair climbing, are nonexercise activities. Combining neuroimaging with ecological assessment of activity and GPS-triggered smartphone diaries, we show a specific association of nonexercise activity with energy in two independent samples mediated by the subgenual part of the anterior cingulate cortex (sgACC), a key emotion regulatory site. Furthermore, energy predicted a range of mental health metrics. sgACC volume moderated humans’ emotional gain from nonexercise activity in real life: Individuals with low sgACC volume, a risk factor for depression, felt less energized when inactive but benefited more from periods of high nonexercise activity. This suggests an everyday life mechanism affecting affective well-being in the general population and, if substantiated in patient samples, a risk and resilience process for mood disorders. - A neural mechanism underlying the real-life effects of nonexercise activity on well-being promises novel intervention targets. - A neural mechanism underlying the real-life effects of nonexercise activity on well-being promises novel intervention targets.
Gesehen am 07.06.2021